2022
DOI: 10.1099/ijsem.0.005407
|View full text |Cite
|
Sign up to set email alerts
|

Duganella vulcania sp. nov., Rugamonas fusca sp. nov., Rugamonas brunnea sp. nov. and Rugamonas apoptosis sp. nov., isolated from subtropical streams, and phylogenomic analyses of the genera Janthinobacterium, Duganella, Rugamonas, Pseudoduganella and Massilia

Abstract: Six Gram-stain-negative, catalase- and oxidase-positive, rod-shaped and motile strains (FT81WT, FT82W, FT107W, FT3ST, LX20WT and LX47WT) sharing high 16S rRNA gene sequence similarities with species of the genera Janthinobacterium (97.0–98.3 %), Duganella (96.3–98.8 %), Rugamonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…mixta is 67 %). As mentioned above genome wide analyses indicate species of the genus Massilia belong to new genera besides those already transferred to genus Pseudoduganella [2]. To examine the species content more deeply, genomes of what is currently Massilia were obtained for eight Massilia species type strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…mixta is 67 %). As mentioned above genome wide analyses indicate species of the genus Massilia belong to new genera besides those already transferred to genus Pseudoduganella [2]. To examine the species content more deeply, genomes of what is currently Massilia were obtained for eight Massilia species type strains.…”
Section: Resultsmentioning
confidence: 99%
“…Genome data, including data from metagenomes, clearly indicates Massilia timonae and other related species found in clinical samples are environmental and not host associated (Table S1). Since all the remaining Massilia species are transferred to new genera (as mentioned above) or to Pseudoduganella [2] the name Massilia should be retired from use entirely. Phenotypic information for the genus Telluria compiled from accumulated description papers is shown in Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work provides the first molecular characterization of prodiginines produced by a member of the Massilia genus. Holochová et al (2020) noted the pigmentation and BGC for prodigiosin in four Antarctic Massilia species, and Woodhams et al (2018) examined a mesophilic Massilia (now Pseudoduganella; Lu et al, 2022) for the production of prodigiosins, however none were detected. In our study, mass defect analysis (Figure 8) identified several metabolites congruent with prodiginines detected within similar retention times (5-8 min), including analogs formed from either the addition of oxygen, reduction, or cyclization.…”
Section: Prodigiosin a Molecule Involved In Environmental Adaptationmentioning
confidence: 99%